IBN SINA'S THOUGHTS: RELEVANCE TO THE EDUCATIONAL OBJECTIVES OF THE MODERN ISLAMIC BOARDING SCHOOL BASED ON AL-RIFA'I MALANG - Amrullah; Khalishah Dyah Capriantin; Balya Ziaulhaq Achmadin; Muhtadi Ridwan; Muhammad Samsul Ulum (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
Avicenna (Ibn Sina) was a medieval Islamic philosopher who developed numerous theories, especially those related to education. Many educational institutions have long relied on Avicenna's ideas about the goal of education, but the evolution of education, especially Islamic education, has changed in tandem with improvements in technology and knowledge in society. As a result, the purpose of this study is to examine the relevance of Ibn Sina's educational ideas to modern Islamic education through a case study of the Al-Rifa'ie 2 modern boarding school. This study employs a qualitative descriptive technique, with data gathered by document analysis, interviews, and observations. The findings of this study revealed that Avicenna's beliefs on the aim of education in developing students' potential so that they have perfect reason and noble morals are still highly relevant at the Al-Rifa'ie 2 modern boarding school today. Despite this, numerous methods, equipment, and technology utilized in education continue to evolve in response to new advances. Avicenna's Islamic education remains a source of inspiration for many institutions today. This study has ramifications for how modern Islamic education adapts to change while maintaining the values of Avicenna's teachings.